Clinical and neuropsychological characteristics of euthymic bipolar patients having a history of severe suicide attempt. (6th August 2014) - Olié, E.; Seyller, M.; Beziat, S.; Loftus, J.; Bellivier, F.; Bougerol, T.; Belzeaux, R.; Azorin, J. M.; Gard, S.; Kahn, J. P.; Passerieux, C.; Leboyer, M.; et al.
<x xml:space="preserve">Abstract</x> Objective Identifying bipolar patients at high‐suicide risk is a major health issue. To improve their identification, we compared dimensional and neuropsychological profile of bipolar patients with or without history of suicide attempt, taking into account suicidal severity (i.e. admission to intensive ward). Method A total of 343 adult euthymic bipolar out‐patients recruited in the French FondaMental Advanced Centres of Expertise for Bipolar Disorder were divided into three subgroups: 214 patients without history of suicide attempt, 88 patients with past history of non‐severe suicide attempt and 41 patients with past history of severe suicide attempt. General intellectual functioning, speed of information processing, verbal learning and memory, verbal fluency and executive functioning were assessed. Results Severe suicide attempters had lower affective intensity and lability than non‐severe attempters. Severe suicide attempters outperformed non‐severe attempters for verbal learning and non‐attempters for Stroop word reading part after adjustment for study centre, age, gender, educational level, antipsychotics use, depression score, anxious and addictive comorbidities. Conclusion Neuropsychological tasks commonly used to assess bipolar patients do not seem accurate to identify suicide attempters in euthymic patients. In the future, decision‐making and emotional recognition tasks should be assessed. Moreover, clinical and neuropsychological profiles should be considered together to better define suicidal risk.